THE APPLICATION OF ENVIRONMENTAL MAGNETISM TECHNIQUES FOR POLLUTION ASSESSMENT IN URBAN AND SUBURBAN AREAS IN GREECE: STATE OF THE ART AND CASE STUDIES - Zananiri, I.; Kondopoulou, D.; Spassov, S. (Bulletin of the Geological Society of Greece, 2010)
Environmental magnetism is a comparatively new discipline, applied in Greece only during the last decade for the study of anthropogenic pollution. The rationale of the method is based on the property of iron oxides and sulphides to attract and absorb heavy metals, organic contaminants and even radioactive pollutants. Thus, the measurement of the magnetic susceptibility, both in situ and in the laboratory, along with several other magnetic parameters constitutes a rapid and cost effective technique for characterization and mapping spatial pollution distribution. In order to quantify the correlation between magnetic susceptibility and a specific pollutant for a studied area geochemical analyses are carried out for key samples. Towards the scope of pollution assessment environmental magnetism studies have been recently carried out in the Kozani-Ptolemaida basin and the tanneries of Thessaloniki. The preliminary results of these two cases, characterized by different contaminant sources, i.e. flying ash pollution in the former and heavy metal in the latter, are presented here. In general, the application of magnetic methods proved a useful tool in the assessment of the main sources of pollution and the location of spatial distribution of major contaminants.